SOSIALISASI KESADARAN HUKUM SEJAK DINI: PENCEGAHAN PERUNDUNGAN (ANTI-BULLYING) DAN DAMPAK HUKUMNYA BAGI ANAK DI PANTI ASUHAN YAYASAN NOORDEEN ACEH TENGAH - Shira Thani; Budi Bahreisy; Birrul Walidaini; Johari; Sumiadi (DEVELOPMENT: Journal of Community Engagement, 2026)
Bullying in the orphanage environment is often considered a joke or a disciplinary tradition; this is due to the ignorance of the law (ignorantia juris) by foster children. Acts of bullying have been strictly prohibited in Article 76C of Law Number 35 of 2014. This community service aims to increase legal awareness from an early age regarding the prevention of bullying and its legal impact on children in the Noordeen Foundation Orphanage in Central Aceh. The implementation method is carried out through a participatory educational approach that includes interactive lectures on the Child Protection Law and the Child Criminal Justice System Law, educational video screenings, questions and answers, and the Declaration of Bullying-Free Homes. The measurement of the effectiveness of activities was analyzed using legal awareness theory and social control theory through pre-test and post-test instruments. The results of the service showed a very significant spike in cognitive understanding of foster children, from 35% at the pre-test to 88% at the post-test. This success indicates an awareness from the phase of legal awareness to a substantive law understanding. In addition, the joint declaration strengthens the internal social control bond of the orphanage to reduce seniority in the dormitory. This service concluded that positive legal debriefing for administrators is able to create an orphanage ecosystem that is legally responsive, independent, and child-friendly in a sustainable manner.